1990
DOI: 10.1103/physrevlett.65.537
|View full text |Cite
|
Sign up to set email alerts
|

Rocket measurement of the cosmic-background-radiation mm-wave spectrum

Abstract: We report here the most precise constraint to date on the spectrum of the cosmic background radiation (CBR), obtained from measurements made with a liquid-helium-cooled spectrometer carried above the atmosphere on a rocket. The spectrum is very well fitted by a Planck function of temperature 7=2.736 K. The scatter of the equivalent temperature in the band 3-16 cm -1 is ±10 mK, about j% of the mean whereas the estimated overall accuracy of the mean temperature is ± 17 mK. These results are inconsistent with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(69 citation statements)
references
References 15 publications
2
67
0
Order By: Relevance
“…After Relict and COBE experiments, the CMBR anisotropies and spectrum are well known [218][219][220][221]. The perfect thermal Planck spectrum of the CMBR and its very small anisotropies are among the most important observational cosmological facts.…”
Section: The Cosmic Microwave Background Radiationmentioning
confidence: 99%
“…After Relict and COBE experiments, the CMBR anisotropies and spectrum are well known [218][219][220][221]. The perfect thermal Planck spectrum of the CMBR and its very small anisotropies are among the most important observational cosmological facts.…”
Section: The Cosmic Microwave Background Radiationmentioning
confidence: 99%
“…I gave up (a last example is Peebles 1999) because the rapidly advancing observations were ruling out my models as fast as I could put them on astro-ph, and they were agreeing wonderfully well with CDM. Earlier than that, the beautiful measurements by Mather et al (1990) and Gush, Halpern & Wishnow (1990) had shown that the CMB spectrum is very close to thermal, removing the worry about serious perturbations to the CMB by explosions. Still earlier, Bond & Efstathiou (1987) were willing to put aside my worries and compute.…”
Section: Structure Formation and The Cosmological Testsmentioning
confidence: 99%
“…This theory is, however, currently not yet well understood beyond perturbation theory 11 . For applications to early universe cosmology, however, a non-perturbative understanding will be essential.…”
Section: Principlesmentioning
confidence: 99%
“…The CMB is this remnant gas of photons from the early universe. The precision measurement of the black body nature of the CMB [11] can be viewed as the beginning of the "Golden Age" of observational cosmology. The third observational pillar of Standard Cosmology is the good agreement between the predicted abundances of light elements and the observed ones.…”
Section: B Standard Big Bang Modelmentioning
confidence: 99%